ISLAM PADA MASA KESULTANAN LANGKAT ABAD XX - Abdul Gani Jamora Nasution; Husna Ibrahim; Arwita Putri; Rinanti Ito Pohan; Intan Nuraini (Prodi Tadris Ilmu Pengetahuan Sosial FITK UIN Sumatera Utara Medan, 2022)
Today many people do not know history, especially the history of their own place of residence, in this case history is an important thing for us to know because by knowing history we can know the truth so that the history of a country, place of residence, etc. is not easy. vandalized, stolen by foreigners and so on. Therefore in this historical journal the focus is on reviewing Islam during the 20th century Langkat Sultanate. For this reason, the researcher formulated several problems regarding this research, namely how the biography of the sultan who served in the XX century and what were the policies of the sultan's government in the XX century and what Islamic policies had been achieved by the sultan of the XX century and the causes of the collapse of the Langkat sultanate. In this research we use historical methods which are studied through four stages to get perfect results, namely heuristics, verification, interpretation, and historiography. The purpose of research on Islam during the Langkat Sultanate in the XX century is to thoroughly discuss Islamic leadership during the Langkat Sultanate in the XX century, where in the XX century the Langkat Sultanate was led by 2 Sultans namely Sultan Abdul Aziz and Sultan Mahmud. When the 20th century became the glory of Islam, not only that, but its glory can be seen from many aspects such as the economy, education, politics and others, all of which were at their peak during the time of Sultan Abdul Aziz. However, in the subsequent leadership during the reign of Sultan Mahmud, these aspects experienced a decline and the collapse of the Langkat Sultanate also occurred during the leadership of Sultan Mahmud.Keywords: Islam, the Sultanate of Langkat